IMPLEMENTASI KEBIJAKAN PENATAAN REKLAME PERMANEN DI JALAN BASUKI RAHMAT KECAMATAN TEGALSARI KOTA SURABAYA - Reza Muhammad Nashruddin; Diana Hertati (LPPM Universitas Abdurrab, 2024)
The city of Surabaya is the capital of East Java Province and one of the largest cities in Indonesia. This of course makes many industries operating in the field of goods and services compete to offer and introduce their products in the city of Surabaya. One of the media to introduce these products is through advertising. These advertisements have various forms, one of which is permanent advertisements which are increasingly appearing in the city of Surabaya. Therefore, the Surabaya City Government formulated a policy in order to maintain order in the erection of permanent billboards in the City of Surabaya, as well as in maintaining the security and aesthetics of the city. In realizing the implementation of the permanent advertising arrangement policy in the City of Surabaya, the Surabaya City Government issued Surabaya City Regional Regulation Number 5 of 2019 concerning the Implementation of Billboards and Surabaya Mayor Regulation Number 43 of 2023 concerning Amendments to the Surabaya Mayor Regulation Number 21 of 2018 concerning Procedures for Organizing Advertisements. This permanent advertisement in the city of Surabaya is spread across several roads, one of which is Jalan Basuki Rahmat, Tegalsari District, which is a city road and is a dense area which includes office areas, shopping, hotels, and so on. This research aims to identify, evaluate and describe the permanent advertising arrangement policies implemented on Jalan Basuki Rahmat, Tegalsari District, Surabaya City. The theory used in this research is the policy implementation model theory from Merilee S. Grindle. The type of research used is qualitative research with data collection techniques in the form of observation, interviews and documentation. The results of the research show that the policy for arranging permanent billboards on Jalan Basuki Rahmat, Tegalsari District, Surabaya City is implemented both from a Policy Content focus and an Implementation Environment focus, but there are still obstacles, namely in the implementing department or human resources which are still not optimal at the Surabaya City Regional Revenue Agency. Another obstacle is that there are still individuals or groups who commit violations in the implementation of permanent advertisements.